Exercise alters the molecular pathways of insulin signaling and lipid handling in maternal tissues of obese pregnant mice - Musial, Barbara (Physiol Rep, 2019)
Obesity during gestation adversely affects maternal and infant health both during pregnancy and for long afterwards. However, recent work suggests that a period of maternal exercise during pregnancy can improve metabolic health of the obese mother and her offspring. This study aimed to identify the physiological and molecular impact of exercise on the obese mother during pregnancy that may lead to improved metabolic outcomes. To achieve this, a 20‐min treadmill exercise intervention was performed 5 days a week in diet‐induced obese female mice from 1 week before and up to day 17 of pregnancy. Biometric, biochemical and molecular analyses of maternal tissues and/or plasma were performed on day 19 of pregnancy. We found exercise prevented some of the adverse changes in insulin signaling and lipid metabolic pathways seen in the liver, skeletal muscle and white adipose tissue of sedentary‐obese pregnant dams (p110β, p110α, AKT, SREBP). Exercise also induced changes in the insulin and lipid signaling pathways in obese dams that were different from those observed in control and sedentary‐obese dams. The changes induced by obesity and exercise were tissue‐specific and related to alterations in tissue lipid, protein and glycogen content and plasma insulin, leptin and triglyceride concentrations. We conclude that the beneficial effects of exercise on metabolic outcomes in obese mothers may be related to specific molecular signatures in metabolically active maternal tissues during pregnancy. These findings highlight potential metabolic targets for therapeutic intervention and the importance of lifestyle in reducing the burden of the current obesity epidemic on healthcare systems.